Changes in lip forms on three-dimensional images with alteration of lip support and/or occlusal vertical dimension in complete denture wearers - Ushijima, Masao; Kamashita, Yuji; Nishi, Yasuhiro; Nagaoka, Eiichi (Journal of prosthodontic research, 2013)
This study aimed to examine changes in the lip form, oral fissure form and vermilion height of complete denture wearers resulting from altered occlusal vertical dimension (OVD) and/or lip support. Three-dimensional facial images of 10 edentulous patients (four males and six females) when wearing six experimental record blocks (ExpRBs) with varying OVD and/or lip support were analyzed. Analysis was performed using three landmarks on the mid-line (labrale superius (ls), stomion (sto), and labrale inferius (li)) and two landmarks on the oral fissure (at points 20mm right and left of the midline (r-OFP and l-OFP, respectively)). Curvature of the oral fissure (COF) in the frontal view was evaluated by calculating the difference between sto and the average of r-OFP and l-OFP (avrl-OFP). The vermilion height in the frontal view was calculated as the distance from sto to ls and li. In 10 subjects, comparison between standard ExpRB and test ExpRBs with altered OVD and/or lip support was performed by calculating differences between these data. The ls, sto, and li landmarks changed with alteration of OVD and/or lip support, whereas avrl-OFP changed vertically with alteration of lip support and anteroposteriorly with alteration of OVD and/or lip support. COF and vermilion height were affected by alterations in OVD and/or lip support. Deficient OVD with extensive lip support can curve the oral fissure form upward, and deficient OVD with deficient lip support can reduce the vermilion height.